Do Chairs Reduce a Navigator’s Mobility? Pilot Study on the Influence of Navigation Bridge Design on Lookout Routines - Stopa Michał (Polish Maritime Research)
Despite technological progress in the maritime industry, navigators are still the final link of the decision-making chain and rely not only on equipment, but also on human senses. Visual observation of the vessel’s surroundings still plays a crucial role in navigation. Four different ships in service were visited to investigate the work of professional navigators and carry out a pilot experiment on real crews to test the methods for future full-scale research. The main objective was to better understand the influence of bridge design on lookout routines of navigators, while the additional goals were to check the presence of navigators in certain parts of the bridge and to determine if it is reasonable to forbid navigators to sit, as the practice is still used on some ships. Considering space limitations and differences in layouts of the wheelhouse, rarely mentioned in this kind of study, the movement of watch-keeping officers was analysed. In total, twenty observations were made to generate the heatmaps of presence during the routine duties. The results of the research indicate that many factors, including bridge design and layout of equipment, might affect lookout routines but it is possible to find similar patterns on the bridges of different shapes and arrangements. The pilot experiment confirms that it is reasonable to carry out a full-scale study, as there is still room for improvement in the area of ergonomic bridge design. Better understanding of modern lookout and movement routines might lead to the development of adequate ergonomic regulations and result in increased work comfort and the well-being of seafarers.